Corneal Subbasal Nerve Plexus Evaluation by in Vivo Confocal Microscopy in Multiple Sclerosis: A Potential New Biomarker - Fernandes, Diogo; Luís, Maria; Cardigos, Joana; Xavier, Catarina; Alves, Marta; Papoila, Ana Luísa; Cunha, João Paulo; Ferreira, Joana Tavares (Current eye research, 2021)
Purpose/Aim: Our study aims to evaluate corneal subbasal nerve plexus morphology by in vivo corneal confocal microscopy (CCM) in Multiple Sclerosis (MS) patients and to explore its potential ability to distinguish between MS patients and healthy subjects. Materials and methods: Cross-sectional study, including 60 MS patients and 22 healthy subjects. Expanded Disability Status Scale (EDSS) was used to assess neurological disability. All participants underwent full ophthalmology evaluation, CCM and optical coherence tomography (OCT). Corneal nerve fibre density (CNFD), branch density (CNBD), fibre length (CNFL) and fibre tortuosity (CNFT) were analysed. Generalized additive regression models were used to analyse the data. Results: Compared to controls, MS patients had lower CNFD, CNBD and CNFL (p < .001) and higher CNFT (p = .002). The area under the ROC curve to distinguish MS patients from healthy controls with CNFD and CNBD was 0.84 (95%CI: 0.75 to 0.93; 95%CI: 0.75 to 0.92, respectively). A nonlinear association between EDSS and CNFD was found, with an initial density increase followed by a significant decrease until more severe disability status. EDSS was associated with CNFL and CNBD, with values being significantly lower for patients with an EDSS > 2.5 (−2.06 mm/mm2; 95%CI: −3.84 to −0.28; p = .027 and −8.70 branches/mm2; 95%CI: −14.69 to −2.71; p = .006, respectively). An optic neuritis (ON) history did not influence CCM parameters. Conclusions: Our results confirm CCM parameters' potential to differentiate MS patients from healthy subjects, not being influenced by a previous ON history. A significant relationship between patient's disability and corneal nerve morphology was also found.